Self-reported depression and social support are associated with egocentric network characteristics of HIV-infected women of color - Lynne C. Messer; E. Byrd Quinlivan; Adaora Adimora; Katya Roytburd (BMC, 2020)
Abstract Background We explore the social network characteristics associated with depressive symptoms and social support among HIV-infected women of color (WOC). Methods Network data were collected from 87 HIV-infected WOC at an academic Infectious Disease clinic in the United States (US) south. With validated instruments, interviewers also asked about depressive symptoms, social support, and treatment-specific social support. Linear regression models resulted in beta coefficients and 95% confidence intervals for the relationships among network characteristics, depression, and support provision. Results Financial support provision was associated with lower reported depressive symptoms while emotional support provision was associated with increased reported social support. Talking less than daily to the first person named in her network, the primary alter, was associated with a nearly 3-point decrease in reported social support for respondents. Having people in their social network who knew their HIV status was also important. Conclusions We found that both functional and structural social network characteristics contributed to perceptions of support by HIV-infected WOC.